BobPursley..here it is:

posted by .

Problem 1:
(x-2)/(3x+4) - 6x/(x+1)
What I did:
Common denominator is: (3x+4)(x+1)

(x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4)

[(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4)
(x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4)

x^2 - 18x^2 = -17x^2
-x - 24x = -25x
(-17x^2 - 25x - 2) / (x+1)(3x+4)



I don't see any errors.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math!

    determine two geometreic sequences whose first terms are 18x-9, 2x+8 and x-1 how would I go about and do this question?
  2. Math(Please Help)

    x-2 6x ____ - _____ 3x+4 x+1 *You are supposed to simplify the expresion.I really need help with this and some other problems.Please and Thank you.- Perhaps I could help but I can't make heads or tails of your posts. Try using parentheses …
  3. Algebra (Re.: Reiny)

    The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 + b^2)/ab …
  4. Algebra

    checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
  5. math

    when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left with -18x/(x^(2)-9) or is it just 18x?
  6. college algebra

    y intercept: 3x^2+18x 0=3x^2+18x from here im lost
  7. Algebra

    What is the greatest common factor of the following monomials?
  8. algebra

    -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
  9. Math

    Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+18x-36
  10. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?

More Similar Questions